Analyzing the content of archives in Arabic reading books for the primary stage in the light of children's literature standards (Journal of the College of Basic Education, 2022)
The search aims to:Analysis of the content of the archives in the Arabic reading books for the primary stage in the light of children's literature standards.The research community includes an analysis of the content of the Arabic reading books for the first three stages of the primary school stage.First row: eight archives.The second row: nine archives.Third row: twelve memorized.The researcher used the descriptive approach as a method for his study, and the method of content analysis to achieve the goal of his study, because it is the appropriate way to achieve the desired purpose.And after analyzing the archives for each of the Arabic reading books for the three stages